Postoperative cognitive dysfunction in geriatric patients after orthopedic surgery - Gelmanas, Arūnas; Bukauskas, Tomas; Macas, Andrius; Žarskienė, Giedrė; Žarskus, Ainius (Acta medica Lituanica, 2012)
The aim of our study was to find out the changes of cognitive functions of geriatric patients after orthopedic surgery and when these differen ces are marked. We also tried to find out factors, which have influence on the results of common mental activity, to estimate the dynamics of mental activity and to choose the most optimal intervals of estimation. The population of our investigation consisted of 25 consecutive adult patients, undergoing orthopedic operation, applying regional anesthesia. Neurophysiological assessment where all patients underwent neurophysiological tests consisted of the Mini-mental State Examination (MMSE), 6 Item Cognitive Impairment test (6CIT), Trail-making test – a neuropsychological test of visual attention and task switching. Patients were tested the day before the surgery (MMSE1, 6CIT1, TMT1), on the day of the surgery (MMSE2, 6CIT2, TMT2) and on the third day after the surgery (MMSE3, 6CIT3, TMT3). The day before the surgery reveals that results of MMSE1, 6CIT1 tests were better in a group of younger patients. We found that the results of the MMSE test were significantly worse 3 days after the surgery than those before the procedure in the A group, p = 0.016. The biggest digression was fixed in “copying” and “repeating” after the surgery intervention, p = 0.01, p = 0.04. The orientation in time significantly decreased in the group B after the surgery, p = 0.00. MMSE, 6CIT, TMT test results were significantlt worse in older patients rather than younger ones 3 days after the surgery. We set that the elderly have a significantly shorter duration of education. Younger patients and patients with a longer studying period achieved better results of tests. The results mean that age and lasting of education are significant predictors of POCD. Our pilot study confirmed that POCD develops for older patients, undergoing neuroaxial anesthesia for orthopedic surgery. It is very important to continue studies and reveal how to decrease POCD events, keep the quality of life.